Postharvest quality of green chilli (Capsicum annuum) cultivars under cold and ambient conditions - KAPOOR, SWATI; SIDHU, RAMANDEEP KAUR; TANDON, RITU; JINDAL, S K; MAHAJAN, B V C (The Indian Journal of Agricultural Sciences, 2022)
The objective of the present investigation was to study the shelf-life of green chilli (Capsicum annuum L.) hybrid CH-52 and checks (CH-27 and Veerji) under cold storage and ambient conditions. The study was carried out at Punjab Horticultural Postharvest Technology Centre, Punjab Agricultural University during 2019–20. All the cultivars were packed in LDPE (Low Density Polyethylene) bags of 25 gauge thickness and were stored under cold store (4–7°C ± 1°C) and ambient (25–30°C) conditions. Significant differences were observed among genotypes for various physicochemical characteristics under both the storage conditions. CH-52 recorded lowest weight loss and minimum spoilage. Higher antioxidant potential, chlorophyll and capsaicin were also retained in CH-52 at the end of storage period. Among other two genotypes CH-27 showed better shelf life than Veerji. Therefore, CH-52 could be recommended for commercial cultivation owing to its lowest spoilage index and higher shelf life as compared to checks.